Adaptation Strategies of Generation Z Employees to Traditional Organizational Culture: A Phenomenological Study - Dewa Putu Yohanes Agata L. Sandopart (CV. Global Cendekia Inti, 2026)
Generation Z now constitutes a significant component of the global workforce, yet faces substantial adaptation challenges when entering companies with traditional, hierarchical, and procedural organizational cultures. This study aims to explore the adaptation strategies developed by Generation Z employees in response to tensions between their personal values and the cultural demands of traditional companies. Employing a qualitative approach with an interpretative phenomenological analysis design, this research involved 10 participants working in three established traditional companies within the Greater Jakarta area (Jabodetabek), each operating for a minimum of 25 years. Data were collected through semi-structured in-depth interviews and analyzed using a six-stage interpretative phenomenological analysis procedure. The findings identified five superordinate themes, including fundamental value clashes encompassing flexibility versus rigid procedures, transparency versus information hierarchy, and immediate feedback versus annual evaluations, passive resistance as an initial strategy manifested through quiet non-compliance, work-to-rule, and silent psychological exit, the critical role of direct supervisors as cultural buffers and determinants of personal loyalty, dual identity negotiation through selective conformity and authenticity strain, and reconstruction of loyalty’s meaning from unconditional to conditional or reciprocal. This study also proposes a Three-Phase Adaptation Model for Generation Z in Traditional Companies consisting of disorientation, negotiation, and stabilization or exit. Theoretical contributions include enriching coping theory, extending social identity theory, and introducing the concept of authenticity strain, while practical implications encompass redesigning performance evaluation systems, cross-generational leadership training, and the development of reverse mentoring programs.